The possibility of use of GIS in game management - Barna, Róbert; Honfi, Vid (Acta Agraria Kaposváriensis, 2002)
Somogy County is the one of the most important habitats and hunting places of the red deer. The red deer of Somogy is known and recognized in the world. Besides the income of hunting the damages done by game is important too. Unfortunately at the present time we have no effective dates of game management. The adaptation of GIS could promote in this area.